Changes in bioavailability of sour cherry (Prunus cerasus L.) phenolics and anthocyanins when consumed with dairy food matrices - Oksuz, Tugba (J Food Sci Technol, 2019)
In this study, it is aimed to understand the changes in sour cherry phytochemicals when their co-digestions are simulated in dairy model systems comprising skim milk, non-fat-yoghurt, probiotic yoghurt or cream. These co-digestions were analyzed for their total phenolic and anthocyanin contents, total antioxidant activity (TAA) in addition to phenolic and anthocyanin profiles, individually. Sour cherry phenolics were stable during gastric conditions (120%); 54% lost in pancreatic digestion and being available (59%) in serum available fraction (IN). Anthocyanins were lost both in gastric (30%) and pancreatic digestions (16%), being only little available (0.6%) in IN. Soymilk had inhibitory effects on TAA. Dairy food matrix components evaluated were found to have distinct effects on the measured bioavailability of individual sour cherry phenolics. This study might aid both consumers and industry on selecting the food matrices to aiding increase in bioavailability.